Diagnosis and Recommendation Integrated System (DRIS) for pineapple (Ananas comosus), Honey Gold variety (MD-2) - López-Montoya, Jennifer; Fernández-Paz, Jéssica Alejandra; Vásquez, Herney Darío; Menjivar-Flores, Juan Carlos (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Pineapple (Ananas comosus) is the third most important tropical species and is grown in tropical and subtropical countries. Given the importance of this crop, it is necessary to have a tool for proper nutritional diagnosis. So, the present study sought to determine the DRIS (Integrated Diagnostic and Recommendation System) standards for the cultivation of pineapple, that is, a methodology for the interpretation of foliar analyzes, based mainly on the establishment of reference populations for obtaining norms or ideal relationships of nutrients, which serve for the interpretation of the nutritional content of a certain species. A randomized complete block design was used, with six treatments and four repetitions, based on different fertilization plans, sampling four stages of the crop. A soil with a pH of 3 was used. The results showed deficiencies of B, S and Zn; elements such as Cu and Na showed limitations as a result of excesses, followed by Fe, but only for the first stage, while P was one of the mineral elements that presented a good balance during the entire stage of the crop. The decreasing order of deficiency constraints for the leaf tissue concentrations in the pineapple was divided into four stages of crop development: the first stage 3 months after sowing: Mn>B>S>Ca>K>Mg>Cu>N>P>Zn>Na>Fe, the second stage 6 months after sowing: Zn>B>- Na>Ca>Mn>Mg>K>N>P>S>Cu, the third stage 9 months after sowing: B>Zn>S> Mn>Ca>N>K>P>Mg> Na>Cu, and the last stage 12 months after sowing: B>Zn>Mn>Ca>Mg>N> K>S>Na>P>Cu.